Differences between 2 cryoballoon systems in achieving successful pulmonary vein isolation in patients with challenging anatomies - Shuhei Yamashita, MD; Seiji Takatsuki, MD, PhD, FHRS; Shuhei Yano, MD; Yukihiro Himeno, MD; Koki Yamaoka, MD; Susumu Ibe, MD; Yoshinori Katsumata, MD, PhD; Takahiko Nishiyama, MD, PhD; Takehiro Kimura, MD, PhD, FHRS; Masaki Ieda, MD, PhD (Heart Rhythm O2)
Background: A new technology, the POLAR cryoballoon system, was designed to enhance maneuvering and stabilizing catheter positions with a softer balloon and more deflectable sheath. These novel characteristics may help achieve successful pulmonary vein (PV) isolation in difficult cases when conventional balloons were used. Objective: This study aimed to investigate the differences in the lesion profiles, touch-up radiofrequency ablation (RFA) rate, and anatomical predictors of acute PV isolation between the POLAR and Arctic Front Advance Pro (AFA-Pro). Methods: This retrospective study included 338 consecutive patients who underwent a first cryoballoon ablation for paroxysmal atrial fibrillation at Keio University Hospital from April 2019 to September 2023. Using propensity score matching, we extracted 135 pairs treated with a POLAR or AFA-Pro, compared the procedural outcomes, and explored the anatomical predictors related to successful PV isolations. Results: In the matched cohort of 270 patients (median age 67 years [59–73], 77% male), 1535 cryoballoon applications were delivered for 1063 PVs, and touch-up RFA was performed for 84 PVs in 67 patients. The rate of touch-up RFA was significantly lower for the right inferior PV (RIPV) in the POLAR group (9.8% vs 21.6% P = .013), whereas there was no significant difference for the other PVs. A lower RIPV frontal angle was linearly associated with a more favorable outcome for the POLAR group than for the AFA-Pro group (interaction P = .0385). Conclusion: The touch-up RFA rate for the RIPV was significantly lower in the POLAR group than in the AFA-Pro group, with a particularly pronounced difference for inferiorly oriented RIPVs.